Substitusi Tepung Ubi Jalar Ungu dan Penambahan NaHCO3 pada pembuatan Tortilla Chips (Jurnal Teknologi Pangan, 2018)
Substitusi Tepung Ubi Jalar Ungu dan Penambahan NaHCO3 pada pembuatan Tortilla Chips